The remaining [videorecording (DVD)] - Dechart, Bryan; Pacar, Johnny, 1981-; Sipos, Shaun, 1981- (Sony Pictures Home Entertainment, 2015)
An action-packed supernatural thriller that addresses questions of life, love and belief against an apocalyptic backdrop. A group of close friends gather for a wedding, but the celebration is shattered by a series of cataclysmic events and enemies foretold by biblical end-times prophecies. The survivors face a horrifying, uncertain future as they scramble for safety, but as their world collapses around them in chaos and terror will they choose real life through faith, or just try to survive?